Language and Brand Attitudes: Impact of Script and Sound Matching in Chinese and English - Pan, Yigang; Schmitt, Bernd (Journal of Consumer Psychology, 1996)
Chinese names consist of logographs that represent the meanings of a word, whereas English names consist of alphabetic letters that represent the sound of the word. Therefore, we propose that Chinese brand attitudes are primarily affected by the match between script associations and brand associations, but brand attitudes of English names are primarily affected by the match between sound associations and brand associations. A cross‐cultural study conducted in China and the United States confirms these predictions. These findings add further evidence to the stream of research that shows how structural features of languages and writing systems affect consumer behavior.